"An in vitro study(bacterial) to Evaluate Coronal Sealing Ability of Some Resin Sealers" (Journal of Hama University, 2020)
Aim: the aim of this study is to investigate the coronal seal for three resin based root canal sealers. Materials and Methods: The sample used comprise of  57 single rooted teeth, all these teeth are type I and not treated. All roots are intact and size 25# at most at the apex diameter. The sample has been randomly divided into 3 experimental groups and two control groups were assigned as positive and negative control. The 1st Group:15 teeth were filled with GP points and sealer AH Plus. The 2nd Group:15 teeth were filled with GP points and sealer Endo REZ. The 3rd Group:15 teeth were filled with GP points and sealer AD Seal. All the given groups were filled using lateral condensation technique and then the area surface of tooth was coated with two layers of nail varnish. All surface area of the teeth were coated except the very last 2mm of the apex. A microbial leakage system was used at this point which depends on two chambers. An upper and lower chambers. Etch sample then was treated with enterococcus faecalis as an injection of 0.5mm of brain heart infusion broth which contains enterococcus faecalis at the upper chamber daily for 30 consecutive days. The indicator in which the microbial leakage has actually happened is the turbidity appearance of the nutritional liquid within the lower chamber. Results: The third group has showed microbial leakage in all sample size at the time the study was conducted. Whereas, the 1st and 2nd groups had only showed 40% and 60% of microbial leakage respectively. Conclusions: AH Plus sealer has showed superior properties in terms of sealing potential against enterococcus faecalis compared to Adseal. In addition, there was no important statistical significance when AH Plus sealer was compared to that of EndoREZ.